A scientific forecast on dental research output within the next 20 years using exponential smoothing algorithm - Jafar Kolahi; Saber Khazaei (Wolters Kluwer Medknow Publications, 2017)
Introduction: To report a scientific forecast of the number of published dental articles in the next 20 years. Materials and Methods: On October 12, 2016, to find all dental articles, PubMed was searched via the query "1800/1/1"[PDAT]: "2015/12/31"[PDAT] AND jsubsetd [text]. Relevant limitations were applied to find dental clinical trials, review articles, and free full-text dental articles. Consequently, all PubMed records were exported to a CSV file. To forecast the future dental research output using existing time-based data, the Exponential Triple Smoothing algorithm was used, which is an advanced machine learning algorithm. Data were analyzed by Microsoft Office Excel 2016. Results: Seventy-five (1940-2015) years of human attempts to publish dental articles were explored and 572490 records were found, from which 27244 (4.75%) articles were free full-text, 19238 (3.36%) were clinical trials, and 31853 (5.56%) were reviews. Researchers will publish 19195 dental articles in 2036, among which 917 (4.77%) articles will be clinical trials, 1474 (7.67%) will be review articles, and 5482 (28.55%) will be free full-text articles. Conclusion: Changes may be because of the quantity of research funds. The number of all types of dental articles will increase with an acceptable rate over the next 20 years. Of more interest, the number of free full-text articles will grow more rapidly than other article types.